Innovations in the Development of Private Entrepreneurship in the Republic of Uzbekistan - Saodat Arislanovna Yuldasheva; Azamat Talgatovich Kasimov (Researchparks Publishing, 2022)
This article discusses the development of small business and private entrepreneurship, the creation of a favorable business environment for the widespread development of small business and private entrepreneurship, the main directions of reform in Uzbekistan.